2009
DOI: 10.1037/a0013764
|View full text |Cite
|
Sign up to set email alerts
|

Human judgments of positive and negative causal chains.

Abstract: Three experiments investigated the way participants construct causal chains from experience with the individual links that make up those chains. Participants were presented with contingency information about the relationship between events A and B, as well as events B and C, using trial-by-trial presentations. The A-B and B-C contingencies could be positive, negative, or zero. Although participants had never experienced A and C together, A-C ratings were a multiplicative function of the A-B and B-C contingenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 58 publications
3
43
0
Order By: Relevance
“…4 Example scale used to elicit conditional probability judgments in Experiments 1a and 1b predictions for transitive inferences for the global A→C relation rely on qualitatively correct judgments of the local A→B and B→C relationships. Therefore, following previous research (Baetu & Baker, 2009), we included only participants who correctly judged both local relationships to be positive. In Experiment 1a, 25% of participants failed to meet this criterion in each of the two relations; in Experiment 1b an average of 19% failed in each of the two relations.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…4 Example scale used to elicit conditional probability judgments in Experiments 1a and 1b predictions for transitive inferences for the global A→C relation rely on qualitatively correct judgments of the local A→B and B→C relationships. Therefore, following previous research (Baetu & Baker, 2009), we included only participants who correctly judged both local relationships to be positive. In Experiment 1a, 25% of participants failed to meet this criterion in each of the two relations; in Experiment 1b an average of 19% failed in each of the two relations.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research on causal chains has shown that people make transitive inferences from A to C when observing only relations A→B and B→C (Ahn & Dennis, 2000;Baetu & Baker, 2009). Ahn and Dennis (2000) used a sequential learning paradigm, providing participants with evidence on the covariation of events A and B (fertilizer→level of chemicals in soil) intermixed with evidence about events B and C (chemicals→blooming of flower).…”
Section: Previous Research On Transitive Inferences In Causal Chainsmentioning
confidence: 99%
See 3 more Smart Citations